2017
DOI: 10.7196/samj.2017.v107i8.12271
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors and mortality in children with chronic kidney disease

Abstract: 2, and the CKD V group were on maintenance haemodialysis and peritoneal dialysis.Children with known congenital heart disease, diabetes mellitus, liver disease, active infection, systemic lupus erythematosus and malignancies and those who had had a renal transplant were excluded from the study.All patients had a short demographic and clinical history taken along with a physical examination. Background. Cardiovascular disease (CVD) begins early in children with chronic kidney disease (CKD), and its progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…LDL level has been found to be associated with atherosclerotic disease of the aorta and coronary vessels of children [84]. Another study demonstrated increased TC and decreased albumin levels in children undergoing dialysis who died, which may indicate the role of these disturbances in mortality [85]. Despite the fact that this study, after adjusting for age, failed to demonstrate the significant relationship between TC or albumin and mortality, it seems that the correction of TC and albumin levels in all patients with CKD is important since the results of many studies indicate that these risk factors are predictors of morbidity and mortality in CKD.…”
Section: Risk Associated With Bad Cholesterol Profile and Benefitsmentioning
confidence: 99%
“…LDL level has been found to be associated with atherosclerotic disease of the aorta and coronary vessels of children [84]. Another study demonstrated increased TC and decreased albumin levels in children undergoing dialysis who died, which may indicate the role of these disturbances in mortality [85]. Despite the fact that this study, after adjusting for age, failed to demonstrate the significant relationship between TC or albumin and mortality, it seems that the correction of TC and albumin levels in all patients with CKD is important since the results of many studies indicate that these risk factors are predictors of morbidity and mortality in CKD.…”
Section: Risk Associated With Bad Cholesterol Profile and Benefitsmentioning
confidence: 99%